Effect of seating forces on cement-ceramic adhesion in microtensile bond tests - Marocho, Susana María Salazar [UNESP]; Özcan, Mutlu; Amaral, Regina [UNESP]; Valandro, Luiz Felipe; Bottino, Marco Antonio [UNESP] (Springer Nature, 2013)
Objectives: The aim of this study was to evaluate the effect of different seating forces during cementation in cement-ceramic microtensile bond strength (μTBS). Materials and methods: Forty-five blocks (5 × 5 × 4 mm3) of a glass-infiltrated alumina-based ceramic (In-Ceram Alumina) were fabricated according to the manufacturer's instructions and duplicated in resin composite. Ceramic surfaces were polished, cleaned for 10 min in an ultrasonic bath, silica coated using a laboratory type of air abrasion device, and silanized. Each treated ceramic block was then randomly assigned to five groups (n = 9) and cemented to a composite block under five seating forces (10 g, 50 g, 100 g, 500 g, and 750 g) using a dual-cured resin cement (Panavia F). The ceramic-cement-composite assemblies were cut under coolant water to obtain bar specimens (1 mm × 0. 8 mm2). The μTBS tests were performed in a universal testing machine (1 mm/min). The mean bond strengths values were statistically analyzed using one-way ANOVA (α ≤ 0. 05). Results: Different seating forces resulted in no significant difference in the μTBS results ranging between 13. 1 ± 4. 7 and 18. 8 ± 2. 1 MPa (p = 0. 13) and no significant differences among cement thickness. Conclusions: Excessive seating forces during cementation seem not to affect the μTBS results. Clinical relevance: Excessive forces during the seating of single all-ceramic restorations cementation seem to display the same tensile bond strength to the resin cement. © 2012 Springer-Verlag.
Keywords: Cementation; Glass-infiltrated alumina-based ceramic; Microtensile bond strength; Seating forces